205k views
4 votes
If f(x) = -4x^ - 6x - 1 and g(x) = -x2 - 5x + 3, find (f - g)(x).

O
A. (f - g)(x) = -3x2 - 11x + 2
O B. (f - g)(x) = 5x2 + x + 2
O C. (f – 9)(x) = -3x2 - x - 4
O D. (f - g)(x) = 3x2+x+4

User Anirban
by
4.9k points

1 Answer

4 votes

Answer:

O C. (f – g)(x) = -3x^2 - x - 4

Explanation:

I will assume that f(x) is -4x^2- 6x - 1

f(x) = -4x^2 - 6x - 1

g(x) = -x2 - 5x + 3

(f - g)(x)= -4x^2 - 6x - 1 - (-x2 - 5x + 3)

Distribute the minus sign

(f - g)(x)= -4x^2 - 6x - 1 +x2 + 5x - 3

Combine like terms

(f - g)(x)= -3x^2 - 1x - 4

User Halileohalilei
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.